Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content:1. Emerging Centers in the Northeastern Middle Atlas: Balancing Spatial Organization   and Achieving Sustainable Development - The Case of Zararda CenterDr. Goumihi Mohammed, Dr. Jaouad El-Bazoui, Dr. Abdelouahed Bouberria2. The impact of artificial intelligence techniques on marketing innovation:  an applied study on Mobily company in Saudi ArabiaMs. Maha Mohammed Alotaibi,  Dr. Layla Abed Al-Youbi3. Spatial analysis of urban expansion in Baqaa Governorate using remote sensing techniques and geographic information systems during the period (2000 AD - 2022 AD)Ms. Seham Sayer Al-Shammari, Co-Prof. Haifa Hammoud Al-Shammari4. The role of using social media in family upbringing and social values among students of the University of Nizwa in the Sultanate of OmanDr.Mahfouda Rashid Al-Mushaiqri , Dr. Nasser Salim Al-Mazidi, Dr. Khalifa Ahmed Al-Qasabi, Ms. Jihan Ahmed Al-Kindi, Ms. Shatha Salim Al-Mahrouqi5. Archaeological Excavations in Palestine: The Interplay of Ideology and Archaeology  and Their Impact on the City of Jerusalem and the Blessed Al-Aqsa MosqueMr. Arafat Mohammad Mousa Amro6. The role of United Nations envoys in conflict zones - A case study (Darfur) (2003-2024)Mr. Hamza Khalaf Abu Rumman7. Cognitive Journalism: The Modernizing of Journalism and Issues of Knowledge Industry in The MediaMr. Saud Rubaya Mousa Al-Qahtani8. The Impact of Family Violence on Juvenile Delinquency and the Role of Social Work to Reduce it (A descriptive study)Researcher/ Hassan Mohammed Al-Amri, Prof/ Ismail Al-Sayed Katbakhana
Keywords: Journal of Human and Social Sciences